ELECTRICITY GENERATION FROM LANDFILL GAS - Budisulistiorini, Sri Hapsari (Universitas Diponegoro, 2007)
Energy from renewables has been sought to replace current fossil fuel energy generation. Landfill gas has great potential to generate power since it contains methane 40 to 60%. Utilizing an enhanced landfill gas as fuel for power generator is also beneficial to reduce greenhouse gas emission from landfill otherwise it will escape to the atmosphere. Current technology in power generation from landfill gas includes organic rankine cycle (ORC) and stirling cycle engine (SCE) to add the traditional reciprocating internal combustion engine (ICE) and gas turbine (GT). The state-of-the art power generation technologies have been developed and demonstrated in the US whereas in Australia, landfill gas power plant remains with the conventional ones; reciprocating engine and gas turbine.